Urban Malaria Vector Dynamics in Accra, Ghana: Seasonal Abundance, Species Composition, and Transmission Risk - Abdul Rahim Mohammed Sabtiu; Akuamoah-Boateng, Yaw; Mfum, Owusu-Asenso, Christopher; Anisa, Abdulai,; Sraku, Isaac Kwame; Halou, Daniel Kodjo; Doe, Richard Tettey; Boadu, Emmanuel Nana; Mensah, Sebastian Kow Egyin; Azumah, Judith Dzifa; Sarkodie, Adu-Barima; Awotwe, Lourees Esi; et al. (Gigabyte, 2025)
Urban malaria is an emerging challenge in Sub-Saharan Africa, driven by unplanned urbanization, irrigated farming, and vector adaptation, yet data on urban vectors, their diversity and malaria transmission potential are limited. We assessed Anopheles gambiae s.l. abundance, species composition, and behavior in Accra, Ghana, during dry and rainy seasons of 2023 and 2024 across eleven sites representing different socioeconomic settings. A total of 21,064 host-seeking and 1,619 resting mosquitoes were collected. Abundance was highest in irrigated farming and peri-urban sites, and lowest in low socioeconomic areas. An. gambiae s.s. dominated host-seeking populations, while An. coluzzii dominated resting ones. Findings highlight irrigated farming and peri-urban areas as hotspots, requiring targeted surveillance and control.